Engineered microenvironments and microdevices for modeling the pathophysiology of type 1 diabetes. (April 2019) - Becker, Matthew W.; Simonovich, Jennifer A.; Phelps, Edward A.
Abstract: The pathophysiology of type 1 diabetes is a complex process involving tightly controlled microenvironments, a number of highly specific immune cell – islet cell interactions, and the eventual breaking of immune tolerance leading to beta cell death. Modeling this process can provide researchers with powerful insights into how and when to best provide treatment, but has proven difficult to accurately model due to its complex nature and differences between animal models and humans. Much progress has been made in determining the genetic, molecular, and cellular mechanisms of type 1 diabetes, yet translating that knowledge to clinical treatments remains challenging. Thus, there exists a capabilities gap between understanding the disease pathophysiology and engineering effective clinical treatment strategies. Biomimetic modeling of human type 1 diabetes is a valuable tool to study and manipulate islet function and can be employed to address immunological aspects of type 1 diabetes. This article will review recent advances in this field, and will suggest ways to synergize systems to model and observe the pathophysiology of autoimmune diabetes with bioengineered therapeutic strategies.